Replacement of urban space: Estonian post-war town planning principles and local Stalinist industrial towns - Sultson, Siim (Journal of Architecture and Urbanism, 2016)
The presented paper focuses on Estonian urban space research concerning both replacement of urban heritage and establishment of new urban design within the period of mid 1940s and 1950s. On the one hand, Stalinist principles brought by Soviet occupation reminded independent Estonian 1930s town planning ambitions. On the other hand, the new principles formulated a new paradigm that was unfamiliar to local urban space tradition. Estonian urban space was compelled to follow the Soviet doctrine by concept, forms and building materials. Sometimes suffering irrational demolitions the towns got axially arranged representative, but perspective and functional plans. Some existing towns (for instance Tallinn, Pärnu, Narva) got new centres due to war wreckages and the ideological reasons. Meanwhile new industrial towns as examples of Stalinist utopia were built in East-Estonia during 1940s–1950s in order to exploit local mineral resources by the Soviet regime. In comparison with Tallinn and Pärnu urban space of East-Estonian industrial towns Kohtla-Järve and classified Sillamäe – designed in Leningrad (St. Petersburg) – still need to be researched. Though different from the rest of Estonian towns by details and materials of façades city-like centres of Sillamäe and Kohtla-Järve are rather similar to Tallinn and Pärnu by their composition.